Laser surface treatment of high‐speed tool steel (AISI M2). (18th December 2012) - Yilbas, B. S.; Patel, F.; Karatas, C.
<x xml:space="preserve">Abstract</x> High‐speed tool steel (AISI M2) surface is pre‐prepared to form a thin carbon film containing 5% B4C particles prior to laser treatment process. Morphological and metallurgical changes are examined in the treated layer using electron microscope, energy dispersive spectroscopy, and X‐ray diffraction. The microhardness and the residual stress formed at the treated surfaces are measured for samples with and without B4C particles. It is found that the micro‐stresses formed in the neighborhood of B4C particles at the treated surface contributed to the microhardness enhancement at the surface. This is associated with the mismatch of thermal expansion coefficients between B4C particles and the base alloy. The nitride phases are formed at the treated surface, which also contribute to the microhardness increase at the surface. Copyright © 2012 John Wiley & Sons, Ltd.